The Religious-Ecological Harmony: Civic Responsibility of Christians and Muslims in Caring for the Environment in Sentani Papua: Harmoni Religius-Ekologis: Civic Responsibility Umat Kristen Dan Islam Dalam Merawat Alam Sentani Papua - Godlif Malatuny, Yakob; Kadepa, Daniel; W. Pentury, Jolanti; Labobar, Julianus (Citizenship Education, Faculty of Education, Jambi University, 2025)
This study stems from the ecological tragedy in Sentani, where the 2019 flash flood became a concrete symbol of the consequences of massive deforestation in the Cycloop Mountains. This phenomenon highlights the urgency of expanding the concept of civic responsibility within the framework of Citizenship Education, shifting the focus from the relationship between citizens and the state to the relationship between citizens and nature. Using a descriptive qualitative approach grounded in post-positivism, this study explores the meaning, values, and religious practices of Christian and Islamic communities through in-depth interviews, participatory observation, and documentation. The results of the study show that both religions emphasize ecological responsibility: Islam through the concept of khalifah, which requires the preservation of the earth, and Christianity through the mandate of stewardship of creation. However, field findings reveal a paradox: theological awareness has been formed, but ecological practices are still limited to the private space of places of worship and have not been internalized in public spaces that continue to be plagued by waste, pollution, and forest destruction. The novelty of this research lies in offering a civic ecology framework as a new dimension in Civic Education, where environmental destruction is viewed not only as an ethical violation but also as a betrayal of citizenship. The implications of this research expand the horizon of PKn: from education on law and democracy to education on conservation, which places faith, public ethics, and ecological sustainability as the foundations of 21st-century citizenship. This research contributes to the conceptual and practical development of ecological citizenship in Indonesia.